2011
DOI: 10.1186/1753-6561-5-s5-s2
|View full text |Cite
|
Sign up to set email alerts
|

Health financing in Africa: overview of a dialogue among high level policy makers

Abstract: BackgroundEven though Africa has the highest disease burden compared with other regions, it has the lowest per capita spending on health. In 2007, 27 (51%) out the 53 countries spent less than US$50 per person on health. Almost 30% of the total health expenditure came from governments, 50% from private sources (of which 71% was from out-of-pocket payments by households) and 20% from donors. The purpose of this article is to reflect on the proceedings of the African Union Side Event on Health Financing in the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
109
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(113 citation statements)
references
References 3 publications
2
109
0
2
Order By: Relevance
“…The effect size for each SNP is provided by Almasy et al [6]. For each gene, we define its total effect size as:…”
Section: Resultsmentioning
confidence: 99%
“…The effect size for each SNP is provided by Almasy et al [6]. For each gene, we define its total effect size as:…”
Section: Resultsmentioning
confidence: 99%
“…We found that the convergence of the REML failed because no SNP contributed any phenotypic variation in the simulated model [3]. …”
Section: Resultsmentioning
confidence: 99%
“…The difficulty may come from the challenging underlying simulation model, which involved many rare causal SNPs [6]. BNSL relies on joint and conditional probability tables, for which only limited information gain may be available from rare causal SNPs that affect a common trait.…”
Section: Discussionmentioning
confidence: 99%